Hybridization analysis and mapping of the celesticetin gene cluster revealed genes shared with lincomycin biosynthesis - Cermák, L; Novotná, J; Ságova-Marecková, M; Kopecký, J; Najmanová, L; Janata, J (Folia microbiologica, 2007)
The first insight into celesticetin biosynthetic gene cluster of S. caelestis is presented. The genomic DNA of producing strain was digested, digoxigenin-labeled and hybridized with a set of probes designed according to S. lincolnensis gene sequences. Genes with high homology to the lincomycin biosynthetic genes coding for the predicted common parts of the pathway were identified in S. caelestis. Then, genomic DNA of S. caelestis treated by a multiple digestion was hybridized with five digoxigenin-labeled probes to construct a rough restriction map. Two consecutive islands formed by the genes with a putative function in biosynthesis of the shared saccharide moiety revealed an organization similar to the lincomycin biosynthetic gene cluster. The celesticetin cluster was mapped and essential information was obtained for subsequent steps, i.e. isolation and sequence analysis of the cluster.
Keywords: Streptomyces; antibakteriální látky; Lincosamides; mapování chromozomů; DNA, Bacterial; Nucleic Acid Hybridization; multigenová rodina; Lincomycin; linkomycin; DNA bakterií; regulace genové exprese u bakterií; Blotting, Southern; Anti-Bacterial Agents; Southernův blotting; Gene Expression Regulation, Bacterial; operon; Operon; Chromosome Mapping; hybridizace nukleových kyselin; Restriction Mapping; sekvenční homologie nukleových kyselin; linkosamidy; restrikční mapování; Sequence Homology, Nucleic Acid; Multigene Family